Between Bilingualism and Profession: The Unregulated State of Escort Interpreting in Ngazidja, Comoros - Seutla, Lieketso Agatha; Sly-vania, Armel Azihar (International Journal of Linguistics and Translation Studies, 2026)
This study looks at the practice of escort interpreting in the Comoros Islands, using data collected in Ngazidja. The research objectives sought to describe and explain how escort interpreting is practiced in Comoros, find out those who serve as escort interpreters in Comoros and investigate the status of escort interpreting in Comoros. The findings, which are guided by Trait Theory, Control Theory, Practitioners’ Competition Theory, and Tseng Model, show that escort interpreting is primarily performed by bilingual citizens who do not treat it as full-time employment and frequently see it as a transitional activity. The field is distinguished by the absence of professional associations, a disorganized market, uncertain compensation, and a lack of formal education. Although training emerges as a key solution, the study contends that a broader three-pillar strategy which entails professional education, market regulation, and increased policy and public awareness is required to move the sector towards professionalization. Further research is needed on the quality of escort interpreting in the Comoros